Effect of Genetic Deletion or Pharmacological Antagonism of Tumor Necrosis Factor Alpha on Colitis-associated Carcinogenesis in Mice. Issue 3 (9th January 2015) - Craven, Brian; Zaric, Violeta; Martin, Abigail; Mureau, Coralie; Egan, Laurence John
Abstract : Background: Intestinal inflammation in inflammatory bowel diseases is driven by abnormal levels of proinflammatory cytokines, where tumor necrosis factor (TNF)-α seems to be particularly important. Chronic inflammatory signaling in the colon increases the risk of colorectal cancer, so we sought to evaluate the role of TNF-α in a mouse model of this condition. Methods: TNF −/− mice were treated with azoxymethane/dextran sulfate sodium to induce inflammation and tumorigenesis. Etanercept was used to produce pharmacological ablation of TNF-α in wild-type mice. Subsequent activation of procarcinogenic transcription factor NF-κB and relevant proinflammatory cytokines of the TNF superfamily were measured through immunohistochemistry and quantitative polymerase chain reaction methods. Results: Results showed that the severity of colitis, as assessed by mortality, histological scoring, and cytokine expression levels, was similar or slightly higher in mice lacking TNF-α than in control mice. Activation levels of NF-κB were not influenced by the presence of TNF-α. We also observed upregulated expression of TNF family member TNF-β, TNF receptors 1 and 2 and a variety of other proinflammatory factors in colitis-associated tumors of TNF −/− mice, compared with levels in tumors of control mice. Neither genetic ablation of TNF-α nor pharmacological inhibition of the TNF family using etanercept reduced tumor number. Conclusions: Our results reveal a redundant role for TNF-α in a mouse model of colitis-associated tumorigenesis, indicating a high degree of redundancy in proinflammatory cytokine networks in this model.